Ecologies of blood in Johannesburg vampire fiction. Issue 4 (1st October 2016) - Wright, Timothy
Abstract: This essay reads two contemporary Johannesburg vampire narratives, the film Eternity (2010) and the graphic novel Rebirth (2012), as part of a body of fiction that sees post-apartheid Johannesburg as a laboratory for new forms of life. While recent Johannesburg science fiction has imagined the emergence of new and more fluid forms of being in Johannesburg, the vampire narrative employs a far older and more restrictive type of monster. By virtue of its intimate relationship to blood – with its mythical overtones of racial and national essence – and its peculiarly blank and limited form of being, the vampire is a productive figure for imagining whiteness. In this essay, I examine how the Johannesburg vampire registers the mutations of whiteness in the post-apartheid context. Located in a contaminated and contaminating city of hidden capillaries and networks, vampiric blood runs across and perforates the traditional blood bonds of race, family, and nation. Indeed, dependent on a precarious and potentially diseased resource, the Johannesburg vampire is always on the cusp of dissolving the very whiteness it figures. I am interested in the way in which these vampire narratives alternately reinforce and interrogate what I call the politics of prolongation; that is, in the ways in which their horizontal and entangled "haemopoetics" attempt to displace the genealogical poetics of blood that have traditionally suffused the colonial enterprise and its literature.